Structural Challenges of Knowledge-Based Economy in Iran - Mojtaba Valibeigi; Ahmad Mohammadi; Mojgan Valibeigi (EKO-REGIONAL, 2020)
The knowledge-based firms can both flourish and grow and stimulate employment and economic growth. Iranian Knowledge-based firms’ protection law is the protection of small and medium knowledge-based firms which are at their elementary steps of growth and don’t have enough attraction to investors. Knowledge-based firms’ protection law in Iran faces to serious challenges that causes this law will not reach to its aim, same as the other protection laws for reducing unemployment and increasing the economic growth. The aim of the study is investigating of structural challenges of knowledge-based firms in Iran. First challenge is about the definition of these kind of firms which weren’t designed in accordance to demand and the knowledge economy and the learner's economy has been ignored. Second challenge is related to performance mechanisms in financial support and providing the facilities for these kind of firms, which reveals the weakness of mechanisms against the economic surplus and corruption. These challenges caused gaps including the weakness of needed mechanisms for the illegal subsidy banning, dependent situation of the innovation and prosperity fund, Khosoulati pressures, enterprise approach of the government, governmental inter-authority competition and the weakness of participant attraction of the public and private organizations that hinder the movement towards a knowledge-based economy.